(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper analyzes the contemporary trend of publishing books about exceptional women, written in the field of children’s literature. In the paper, the given trend is put into two contexts: the first context is that of collective biographies of women worthies, with a tradition that goes back to the antiquity, whereas the other one is determined by the genre of women’s portrait. Relying on theoretical works about both genres, the paper shows the ways in which contemporary books about exceptional women are part of the writing of women’s history, and of the construction of women’s identity. The other goal of this analysis is to show the complexity of the supposedly naively conceptualized books, through pointing out the narrative strategies and visual potential being used in the construction of identity.